THE EFFECT OF PROPIONIC ACID ADDITION IN POULTRY DIETS ON THE INTERNAL ORGANS OF BROILER CHICKENS - Rizki Palupi; Fitri Nova Lubis; Raical Demino Lubis (Universitas Syiah Kuala, 2020)
This study aims to determine the effects of adding propionic acid in the poultry diets on the internal organs of broiler chickens. The livestock used were 180 broilers with Cobb strain. This study used a completely randomized design (CRD) consisting of 3 treatments and 6 replications.The treatments in this study consisted of: P0= commercial feed without propionic acid addition; P1= commercial feed with addition of 0.5%propionic acid; and P2= commercial feed with 0.75% propionic acid. The parameters observed included live weight, spleen percentage, gizzardpercentage, liver percentage, and small intestine length. The results showed that the addition of propionic acid in the broiler feed had a significant effect (P0.05) on the live weight and had no significant effect (P0.05) on the percentage of spleen, percentage of gizzard, percentage of liver, and small intestine length. The conclusion of this study was that the addition of propionic acid in poultry feed at a dose of 0.75% did not negatively affect the internal organs and the length of the small intestine of broiler chickens.